FE analysis of cruciform welded joints considering different mechanical properties for base material, heat affected zone and weld metal (Fracture and Structural Integrity, 2014)
The aim of this scientific work was to investigate the behaviour of cruciform welded joints under static loading using a full-field technique: Digital Image Correlation. The material curves, relative to different zones (base  material, heat affected zone, weld), were obtained by hardness measurements, which were done by means of a fully automated hardness scanner with high resolution. This innovative technique, based on the UCI method, allowed to identify the different zones and to assess their different mechanical properties, which were considered in the finite element model. Finally the finite element model was validated experimentally, comparing the results with the measurements obtained using the Digital Image Correlation technique.
Keywords: Cruciform welded joints